2011
DOI: 10.1007/s10535-011-0040-8
|View full text |Cite
|
Sign up to set email alerts
|

Improving cucumber photosynthetic capacity under NaCl stress by grafting onto two salt-tolerant pumpkin rootstocks

Abstract: Özet: Aşılı fide, dünyanın birçok ülkesinde sebze yetiştiriciliğinde yaygın olarak kullanılmaya başlamıştır. Aşılı karpuz, kavun ve hıyar yetiştiriciliğinde; tuzluluk problemi olan arazilerde kestane kabağı ve bal kabaklarının, anaç olarak kullanımı önerilmektedir. Bu çalışmada, tuza tolerant olarak belirlenen ümitvar kestane kabağı ve bal kabağı anaçlarının hipokotil özellikleri ve hıyar ile aşı başarı oranları incelenmiştir. Gordion hıyar çeşidi, kalem olarak kullanılmıştır. Genotipler arasında en uzun hipok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 41 publications
4
10
0
4
Order By: Relevance
“…1A,2A). Our findings are in accordance with the results which has been reported in cucumber (Huang et al 2011), winter radish (Munir et al 2013), and cotton (Shaheen et al 2012) cultivars.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…1A,2A). Our findings are in accordance with the results which has been reported in cucumber (Huang et al 2011), winter radish (Munir et al 2013), and cotton (Shaheen et al 2012) cultivars.…”
Section: Discussionsupporting
confidence: 94%
“…Growth inhibition observed in many plants exposed to salinity stress is often associated with a decrease in their photosynthetic capacity (Jiang et al 2006). The salinity-induced decrease in photosynthesis may involve stomatal and nonstomatal limitations and inhibition of photochemical processes (Hichem et al 2009, Huang et al 2011. A substantial inhibition of photosynthesis under salt conditions seems to be associated with degradation of chlorophyll (Chl) (Meng et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…(Sadak et al, 2013) who reported that, leaf area values was significantly decreased by increasing of sodium chloride level. Similar results were reported by (Ghoulam et al, 2002, Abu-Romman et al, 2014and Hung, 2011.…”
Section: Resultssupporting
confidence: 90%
“…One possibility is that autophagy might be responsible for degrading oxidized proteins under salt stress (Liu et al 2009). But in the presence of AsA, the soluble protein content increased, indicating that it may have an important role in plant adaptation to a high NaCl content (Huang et al 2011). Possibly, the protective effect of AsA under salinity stress is more related to a reduction in ROS damages to essential proteins and/or nucleic acids (Noctor and Foyer 1998;Smirnoff and Wheeler 2000;Khan et al 2011).…”
Section: Discussionmentioning
confidence: 99%